THE EFFECT OF ULTRASONIC DIFFUSER ON INDOOR AIR QUALITY - Rimdjonoka, Renāta; Veignere, Elizabete; Laicāns, Ivars; Martinsone, Žanna; Skadiņš, Ingus (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The usage of ultrasonic diffusers in indoors has raised concerns regarding their potential health effects, mostly due to the lack of research on the matter. This study’s aim was to analyse the effect of distilled water, tap water, and tap water with essential oils droplets from an ultrasonic diffuser on the number of particle matter and microbiological contamination in indoor air under laboratory conditions during summer and winter seasons. The most common species throughout all experiments were the Gram+ Aerococcus viridans and Micrococcus luteus, accounting for 21.33% (93 CFU/m3) and 13.76% (60 CFU/m 3) of the total bacteria count. Four different fungal species were identified over both seasons, moulds were more common making up 81.25% (65 CFU/m 3). It was noted that the microorganisms identified were not pathogenic, presenting no significant infection risk from the diffuser's use. Experiments involving the use of an ultrasonic diffuser with DW demonstrated that PM1, PM2.5, and PM10 levels can be maintained within acceptable ranges over a 4-hour period. However, these experiments also highlighted an increase in nanoparticle concentrations, for which current guidelines lack specific recommendations. The diffuser was cleaned before every experimental setup stage, avoiding any residual contamination.